Distinct Pseudomonas type‐III effectors use a cleavable transit peptide to target chloroplasts. (28th December 2013) - Li, Guangyong; Froehlich, John E.; Elowsky, Christian; Msanne, Joseph; Ostosh, Andrew C.; Zhang, Chi; Awada, Tala; Alfano, James R.
Summary The pathogen Pseudomonas syringae requires a type‐III protein secretion system and the effector proteins it injects into plant cells for pathogenesis. The primary role for P. syringae type‐III effectors is the suppression of plant immunity. The P. syringae pv. tomato DC3000 HopK1 type‐III effector was known to suppress the hypersensitive response (HR), a programmed cell death response associated with effector‐triggered immunity. Here we show that DC3000 hopK1 mutants are reduced in their ability to grow in Arabidopsis, and produce reduced disease symptoms. Arabidopsis transgenically expressing HopK1 are reduced in PAMP‐triggered immune responses compared with wild‐type plants. An N‐terminal region of HopK1 shares similarity with the corresponding region in the well‐studied type‐III effector AvrRps4; however, their C‐terminal regions are dissimilar, indicating that they have different effector activities. HopK1 is processed in planta at the same processing site found in AvrRps4. The processed forms of HopK1 and AvrRps4 are chloroplast localized, indicating that the shared N‐terminal regions of these type‐III effectors represent a chloroplast transit peptide. The HopK1 contribution to virulence and the ability of HopK1 and AvrRps4 to suppress immunity required their respective transit peptides, but the AvrRps4‐induced HR did not. Our results suggest that a primary virulence target of these type‐III effectors resides in chloroplasts, and that the recognition of AvrRps4 by the plant immune system occurs elsewhere. Moreover, our results reveal that distinct type‐III effectors use a cleavable transit peptide to localize to chloroplasts, and that targets within this organelle are important for immunity.